Comparative Effectiveness and Economic Evaluations of Open Versus Minimally Invasive Posterior or Transforaminal Lumbar Interbody Fusion: A Systematic Review - Goldstein, Christina L; Phillips, Frank M; Rampersaud, Y Raja (Spine (Philadelphia, Pa. 1976), 2016)
Systematic review of randomized and nonrandomized comparative studies. To summarize the literature examining comparative effectiveness and economic evaluation of minimally invasive versus open transforaminal/posterior lumbar interbody fusion (T/PLIF). Minimally invasive approaches to lumbar fusion have been proposed as an alternative to open surgery to decrease patient morbidity and improve clinical and patient-reported outcomes, with the possibility of secondary cost-savings. The comparative clinical and economic effectiveness of minimally invasive versus open T/PLIF remains largely undetermined. A systematic review of Medline, EMBASE, Web of Science, and Cochrane from database inception to September 2015 inclusive was performed. Reference lists were manually searched. Studies comparing MIS to open T/PLIF for degenerative lumbar conditions, including at least 10 patients in each arm and reporting at least one clinical, perioperative, radiographic, adverse event, or economic outcome, were included. Between database inception and October 2015, 45 studies meeting inclusion criteria were identified with 3472 subjects undergoing MIS fusion and 5925 having an open procedure. There were no significant differences in operative time between the two groups, whereas patients undergoing MIS fusion consistently demonstrated less blood loss (16.1-88.7%) and shorter hospital stays (15.0-64.0% shorter). There was no difference in variably reported VAS, ODI, SF-36, SF-12, or EQ-5D scores between the two techniques at intermediate to long-term follow-up (12-60 months). Complication rates and fusion rates were also equivalent between the two groups. Economic studies demonstrate cost-savings in favor of MIS fusion ranging from 2.5 to 49.3%. Limited quality comparative observational cohort and randomized controlled studies of MIS versus open T/PLIF consistently demonstrate improved perioperative outcomes including operative time, estimated blood loss, and length of stay with no significant difference in patient-reported outcomes or complication rates between the two groups at final follow-up. Increasing economic data suggest both direct and indirect cost-savings in favor of MIS fusion. N/A.